Seroprevalence of seven arboviruses of public health importance in sub-Saharan Africa: a systematic review and meta-analysis - Philippe Vanhems; Alexandre Delamou; Eric D’Ortenzio; Eric Delaporte; Sidikiba Sidibé; Alioune Camara; Salifou Talassone Bangoura; Lanceï Kaba; Aminata Mbaye; Castro Gbêmêmali Hounmenou; Alhassane Diallo; Saidouba Cherif Camara; et al. (BMJ Global Health, 2024)
Background The arboviruses continue to be a threat to public health and socioeconomic development in sub-Saharan Africa (SSA). Seroprevalence surveys can be used as a population surveillance strategy for arboviruses in the absence of treatment and vaccines for most arboviruses, guiding the public health interventions. The objective of this study was to analyse the seroprevalence of arboviruses in SSA through a systematic review and meta-analysis.Methods We searched PubMed/MEDLINE, Web of Science, Embase, Scopus and ScienceDirect databases for articles published between 2000 and 2022 reporting the seroprevalence of immunoglobulin G (IgG) antibodies to seven arboviruses in various human populations residing in SSA. The included studies were assessed using the checklist for assessing the risk of bias in prevalence studies, and the data were extracted using a standard form. A random effects model was used to estimate pooled seroprevalences. The potential sources of heterogeneity were explored through subgroup analyses and meta-regression. The protocol had been previously registered on International Prospective Register of Systematic Reviews with the identifier: CRD42022377946.Results A total of 165 studies from 27 countries, comprising 186 332 participants, were included. Of these, 141 were low-risk and 24 were moderate-risk. The pooled IgG seroprevalence was 23.7% (17.9–30.0%) for Chikungunya virus, 22.7% (17.5–28.4%) for dengue virus, 22.6% (14.1–32.5%) for West Nile virus, 16.4% (7.1–28.5%) for yellow fever virus, 13.1% (6.4–21.7%) for Zika virus, 9.2% (6.5–12.3%) for Rift Valley fever virus and 6.0% (3.1–9.7) for Crimean–Congo haemorrhagic fever virus. Subgroup and meta-regression analyses showed that seroprevalence differed considerably between countries, study populations, specific age categories, sample sizes and laboratory methods.Conclusion This SRMA provides information on the significant circulation of various arboviruses in SSA, which is essential for the adoption and planning of vaccines. These findings suggest the need to invest in surveillance and research activities on arbovirus in SSA countries to increase our understanding of their epidemiology to prevent and respond to future epidemics.